Association of race/ethnicity and insurance with survival in patients with diffuse large B‐cell lymphoma in a large real‐world cohort - Yanling Jin; Jia Li; Yong Mun; Anthony Masaquel; Sylvia Hu; Juliana M. L. Biondo (Cancer Medicine)
Abstract Objective Few studies have evaluated disparities in race, ethnicity, and health insurance in real‐world health outcomes for patients with diffuse large B‐cell lymphoma (DLBCL). This study aimed to evaluate association between racial disparities and health insurance with real‐world health outcomes. Methods Patients with DLBCL (January 2011–July 2021) treated with first‐line therapy were selected from a real‐world database. Variables of interest included race/ethnicity, health insurance type (Medicaid, Commercial) by patient age (<65, ≥65 years), stage at diagnosis, overall survival (OS), and time to second‐line therapy or death due to any cause (TTNTD). Results Among 5362 patients with DLBCL (82% White, 7% Black, 8% Hispanic/Latino, 3% Asian), White patients were older (mean age, 66.7 vs. 59.3–62.5 years) and less likely to have Medicaid insurance (1.7% vs. 3.4%–5.9%). Adjusted hazard ratios (aHR) for OS (Black, 0.88 [95% confidence interval, 0.72–1.07]; Hispanic/Latino, 0.84 [0.70–1.03]; Asian, 0.82 [0.59–1.16]) and TTNTD (Black, 0.89 [0.75–1.05]; Hispanic/Latino, 0.85 [0.73–1.00]; Asian, 1.11 [0.86–1.43]) were similar to those of White patients. Among patients aged <65 years, Medicaid‐insured versus Commercially insured patients had more advanced disease (stage III–IV, 66% vs. 48%), worse OS (aHR, 0.52 [0.34–0.80]; p = 0.003), and shorter TTNTD (aHR, 0.70 [0.49–0.99]; p = 0.044). Conclusions There was no statistically significant difference in these variables/outcomes between Medicaid‐insured and commercially insured patients aged ≥65 years. Medicaid‐insured status was significantly associated with poorer OS and TTNTD in patients with DLBCL aged <65 years but not in those aged ≥65 years, with or without adjusting for other baseline characteristics. Race was not significantly associated with these outcomes.